2011
DOI: 10.1111/j.1601-0825.2011.01862.x
|View full text |Cite
|
Sign up to set email alerts
|

Cleidocranial dysplasia: oral features and genetic analysis of 11 patients

Abstract: The current findings suggest a correlation between dental alterations and mutations in the runt domain of RUNX2 in CCD patients. Further clinical and genetic studies are needed to clarify the relationship between phenotypes and genotypes in CCD and to identify other factors that might influence the clinical features of this uncommon disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
43
0
12

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(59 citation statements)
references
References 25 publications
(42 reference statements)
3
43
0
12
Order By: Relevance
“…It is intriguing that the recent sequencing of the Neanderthal genome provides evidence for positive selection in the modern human variant of one of these key genes, RUNX2, which is known to affect MS fusion (26). RUNX2-related disorders, such as cleidocranial dysplasia, result in delayed MS fusion and pathologies, such as extreme bulging of the forehead and hypertelorism (27). Premature closure of the metopic suture (metopic synostosis), on the other hand, typically results in trigonocephaly: that is, a narrow forehead with an external metopic ridge (keel) extending from glabella to the midforehead, relatively close-set orbits and no lateral browridge (28,29).…”
Section: Discussionmentioning
confidence: 99%
“…It is intriguing that the recent sequencing of the Neanderthal genome provides evidence for positive selection in the modern human variant of one of these key genes, RUNX2, which is known to affect MS fusion (26). RUNX2-related disorders, such as cleidocranial dysplasia, result in delayed MS fusion and pathologies, such as extreme bulging of the forehead and hypertelorism (27). Premature closure of the metopic suture (metopic synostosis), on the other hand, typically results in trigonocephaly: that is, a narrow forehead with an external metopic ridge (keel) extending from glabella to the midforehead, relatively close-set orbits and no lateral browridge (28,29).…”
Section: Discussionmentioning
confidence: 99%
“…Cleidocranial dysplasia (CCD), which is caused by mutation of Runx2, is a hereditary congenital disorder characterized by the abnormalities of bone development such as clavicle dysplasia, unclosed fontanels, and retained primary teeth due to no root resorption [11][12][13][14][15][16]. Previous studies reported that Runx2, which is the master osteogenic transgenic factor regulating osteogenesis metabolism, also induces differentiation of osteoclast through regulation of RANKL and OPG [17][18][19][20][21].…”
mentioning
confidence: 99%
“…La malformación de los huesos del cráneo puede provocar hipoacusia 8 , siendo esta una complicación frecuente y que debe buscarse de forma dirigida.…”
Section: Discussionunclassified